2(x+10)+4=6(x-10)

Simple and best practice solution for 2(x+10)+4=6(x-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+10)+4=6(x-10) equation:


Simplifying
2(x + 10) + 4 = 6(x + -10)

Reorder the terms:
2(10 + x) + 4 = 6(x + -10)
(10 * 2 + x * 2) + 4 = 6(x + -10)
(20 + 2x) + 4 = 6(x + -10)

Reorder the terms:
20 + 4 + 2x = 6(x + -10)

Combine like terms: 20 + 4 = 24
24 + 2x = 6(x + -10)

Reorder the terms:
24 + 2x = 6(-10 + x)
24 + 2x = (-10 * 6 + x * 6)
24 + 2x = (-60 + 6x)

Solving
24 + 2x = -60 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
24 + 2x + -6x = -60 + 6x + -6x

Combine like terms: 2x + -6x = -4x
24 + -4x = -60 + 6x + -6x

Combine like terms: 6x + -6x = 0
24 + -4x = -60 + 0
24 + -4x = -60

Add '-24' to each side of the equation.
24 + -24 + -4x = -60 + -24

Combine like terms: 24 + -24 = 0
0 + -4x = -60 + -24
-4x = -60 + -24

Combine like terms: -60 + -24 = -84
-4x = -84

Divide each side by '-4'.
x = 21

Simplifying
x = 21

See similar equations:

| x+81+88=400 | | (-16z^3)(9yz)= | | 2p+10=9+3p | | L*2=L*5-6 | | 6n^2+7=31 | | 2(6x+8)+2(8x+6)=16(4x+2) | | (4z^5)(12yz)= | | 2mr(-6mr^6)= | | 2(9x+12)+2(12x+9)=24(6x+3) | | (2xy^3)(6x^4)= | | (-6ab^2)(-9bc)= | | 23x^2-34x=0 | | (9ay)(-8y)= | | (5x^2y^3)(5x^2y^3)= | | 2+(3*w)=12+(2*w) | | (8b^3cd)(2b)= | | 15x^2-59x+56=0 | | (6a^5b^6)(3ab)= | | -(x+1)+2x-6=7 | | 17b=9.4 | | 3(2a+1)-5a=5-3 | | -2(x-6)+3x=7-9 | | 3(x+4)-2x=2 | | (9x^3+5x^2-4x)-(5x^3-2x^2-6x)-(4x^3+6x^2+24)=0 | | 9(-2-9a)-5=103-81a | | 4-8=6x-5x+9 | | X+5y=2x+38 | | 2t+3=21-4t | | 2a-5-a=-4+7 | | 17b-2=-7.4 | | (7m^2n^2)(m^6n^2)= | | 3a+6-2a=5 |

Equations solver categories